Pemberdayaan KPM PKH melalui Pendidikan dan Pengaturan Ekonomi Keluarga - Warsidi Warsidi; Airlangga Surya Kusuma; Faizi Faizi; Jubei Levianto; Abdul Aji Kresna Tri Anggara (Universitas Prof. Dr. Moestopo (Beragama), 2026)
Beneficiaries of the Family Hope Program (PKH) require practical empowerment not only in receiving social assistance, but also in transforming the assistance into better family welfare through education-oriented priorities and household economic management. This community engagement program aimed to strengthen the understanding of PKH beneficiary families in Tanjungbaru Village, Cikarang Timur, Bekasi, regarding education planning, income and expense recording, monthly budgeting, debt control, and emergency fund preparation. The activity was conducted offline on 17 April 2026 and involved 23 PKH beneficiaries. The method consisted of preparation and coordination, a pre-test, interactive socialization, discussion of household financial cases, and a post-test. The results showed an increase in participants’ average score from 1.93 in the pre-test to 3.96 in the post-test, or an average improvement of 2.03 points. The most visible improvements occurred in participants’ understanding of education fund planning, debt management, emergency funds, and business capital planning. These findings indicate that structured and contextual financial education can improve the capacity of PKH beneficiary families to regulate household expenditure, prioritize children’s education, and reduce the risk of unproductive debt. Sustainable mentoring involving PKH facilitators and local community actors is recommended to ensure behavioral changes and long-term welfare improvement.